Effect of dietary n-6 to n-3 polyunsaturated fatty acid ratio on prostaglandin plasma levels and genes expression peroxisome proliferator-activated receptor (PPAR) in pregnant Sprague Dawley rats - Ali, Amira Abdulbari; Abu Bakar @ Zakaria, Md Zuki; Goh, Yong Meng; Mohamed Mustapha, Noordin (Academic Journals, 2011)
The peroxisome proliferator-activated receptors (PPARs) are a family of nuclear transcription factors thought to act as receptors for polyunsaturated fatty acids and to reduce production of series 2 prostaglandins (PG). The objective of this study was to investigate the effect of different ratio n-6: n-3 on the PPAR expression of rats endometrial tissue. The findings obtained from this study showed significant induction of PPARδ mRNA levels in endomatral cells treatment 1:1 group by 1.38 fold compared with the PPARδ mRNA levels in endomatral cells treatment 30:1 group. This induction was due to the cellular demands for prostaglandin were high in the endometrial cells when cells were treated with high ratio n6:n3 on 30:1 group, thus, resulting in an increase in both prostaglandin PGE2 and PGF2α production by induction of PPARδ genes. On the other hand, treatment 1:1 group and control group of endometrial cells did not show any significant changes in mRNA level of PPARδ, compared with treatment ratio n6:n3 on 6:1 group and treatment high ratio n6:n3 on 30:1 group of the endometrial cells. These findings show that inhibit ion of uterine PGF2α synthesis by n-3 fatty acids may depend on the amount of n-6 fatty acids reaching the target tissue. In conclusion, PPARδ function in the response of rat endometrium to long chain n-6:n3 polyunsaturated fatty acids.